2013
DOI: 10.1186/1471-2458-13-281
|View full text |Cite
|
Sign up to set email alerts
|

Late presenters among persons with a new HIV diagnosis in Italy, 2010–2011

Abstract: BackgroundIn Western Europe, about 50% of newly diagnosed HIV-positive individuals are diagnosed at a late stage disease and enter in care late (i.e. with a CD4 count ≤350 μL/μL). The aim of the present study is to analyze the characteristics and the factors associated with being diagnosed late or at an advanced stage of disease among persons with a new HIV diagnosis in Italy, in the period 2010–2011.MethodsWe used individual data on new HIV diagnoses reported by the HIV surveillance system in 2010 and in 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
36
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 18 publications
13
36
2
4
Order By: Relevance
“…T cell count. As reported by many studies conducted in Italy as well as in other European countries, a relevant proportion of infected patients actually get to diagnosis when immunological and clinical conditions are severely compromised [17,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 93%
“…T cell count. As reported by many studies conducted in Italy as well as in other European countries, a relevant proportion of infected patients actually get to diagnosis when immunological and clinical conditions are severely compromised [17,[22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 93%
“…The decreases in late presentation are likely associated with changes to provider initiated HIV testing policies and the massive scale-up of antenatal screening for HIV [20],[21]. Factors associated with late presentation in this and previous studies included non-MSMs HIV-exposure group [1],[5],[14],[16],[17],[22], older age [1],[14],[16][19],[23], and non-European origin [14],[17],[19],[22],[24]. Reasons for the increase in late presentation among IDUs in Eastern Europe and heterosexual females and male IDUs from Southern Europe may include suboptimal health care offered to these populations, differences in characteristics that we were unable to adjust for, such as socioeconomic status, the pattern of the underlying epidemic, and appearance of symptoms that may ultimately promote presentation for care [25],[26].…”
Section: Discussionmentioning
confidence: 96%
“…28,29 Late-diagnosed patients would be expected to be older than patients diagnosed for other reasons because HIV-related symptoms usually develop after a prolonged period of infection at which point immune system has been weakened. 30,31 In addition, a previous study reported that older patients was more likely to be diagnosed during hospitalization, and they suggested that these populations may have lower perceived risk for HIV infection.…”
Section: Discussionmentioning
confidence: 99%